Lonely and scrolling during the COVID-19 pandemic: understanding the problematic social media use and mental health link among university students - Ghanayem, Leen K.; Shannon, Holly; Khodr, Lida; McQuaid, Robyn J.; Hellemans, Kim G.C. (Frontiers in Psychiatry, 2024)
Introduction Undergraduate university students experienced many academic and non-academic stressors during the first year of the coronavirus (COVID-19) pandemic, putting them at a greater risk of negative mental health outcomes. Reports worldwide have shown high incidences of depressive, anxiety, and stress scores among university students at the beginning of the pandemic. Emerging evidence also suggests that to cope with the stress and loneliness of the pandemic, many youth and young adults increased the amount of time they spent on social media platforms. Methods Undergraduate students participated in an online study aimed to understand the link between time spent on social media, coping through the use of social media and problematic social media use (PSMU) with mental health symptoms, such as stress, depression, anxiety, and loneliness, during the COVID-19 pandemic. Results While time spent on social media was only weakly associated with stress, depression, anxiety and loneliness scores, PSMU more strongly mapped onto these outcomes. Additionally, students who were coping highly using social media displayed elevated stress, depression, anxiety and loneliness levels in comparison to those reporting low levels of coping with social media. Finally, students who reported high levels of coping using social media displayed higher PSMU scores, with this relationship appearing more pronounced in students who had higher levels of loneliness. Conclusion These data support evidence that it is not necessarily time spent on social media but rather PSMU that is relevant for mental health symptoms, and that PSMU is exacerbated by loneliness. Moreover, the current results highlight the effects of maladaptive coping on mental health symptoms and PSMU among university students during the COVID-19 pandemic.